Velocity preserving transfer between highly excited atomic states: black body radiation and collisions. (17th February 2021) - de Aquino Carvalho, J C; Maurin, I; Failache, H; Bloch, D; Laliotis, A
Abstract: We study the excitation redistribution from cesium 7P1/2 or 7P3/2 to neighboring energy levels by black body radiation (BBR) and inter atomic collisions using pump-probe spectroscopy inside a vapor cell. At low vapor densities we measure redistribution of the initial, velocity-selected, atomic excitation by BBR. This redistribution preserves the selected atomic velocities allowing us to perform high resolution spectroscopy of the 6D → 7F transitions. This transfer mechanism could also be used to perform sub-Doppler spectroscopy of the cesium highly-excited nG levels. At high densities we observe interatomic collisions redistributing the excitation within the cesium 7P fine and hyperfine structure. We show that 7P redistribution involves state-changing collisions that preserve the initial selection of atomic velocities. These redistribution mechanisms can be of importance for experiments probing high lying excited states in dense alkali vapor.